Enhancing Sustainability Awareness and Creative Thinking Skills through Free Inquiry Learning - Henita Henita; Atep Sujana; Maulia Depriya Kembara (Universitas Muhammadiyah Mataram, 2026)
Developing creative thinking skills and sustainability awareness is an important challenge in science learning, especially in dealing with global issues related to sustainability. However, prior studies have often emphasized guided inquiry or project-based approaches, while empirical evidence on the effectiveness of free inquiry particularly in simultaneously strengthening creative thinking and sustainability awareness at the junior high school level remains limited, creating a scientific urgency to test its impact in authentic classroom settings. This research aims to analyze the effectiveness of implementing free inquiry learning model in improving junior high school students' creative thinking skills and sustainability awareness. The research used a quasi-experimental method with a matching-only pretest–posttest control group design involving 60 class IX students, consisting of an experimental class and a control class. Research instruments include creative thinking skills tests, sustainability awareness questionnaires, and learning implementation observation sheets. Data analysis was carried out using quantitative techniques and conclusions were drawn based on samples using statistical tests. The research results show that the implementation of free inquiry model is in the very good category. The increase in students' creative thinking skills in the experimental class was moderate and higher than the control class. Apart from that, the sustainability awareness of experimental class students increased significantly and had a strong positive relationship with creative thinking skills. Statistical testing indicated significant posttest differences between groups (p < 0.05), supported by higher learning gains in the experimental class (N-gain = 0.45) compared to the control class (N-gain = 0.30), with the strongest improvements observed in originality and the conceptual–experiential dimensions of sustainability awareness. These findings indicate that free inquiry model is effective in developing students' 21st century competencies.